(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article aimed to identify the intersections between the artistic work of Tadeusz Kantor and the thought of Aby Warburg. From an analysis of Kantor’s work, influenced by its relationship with the plastic arts, it’s evident points of approximation with the logic behind the Mnemosyne Atlas were emphasized. Recognizing the image as the central point of the parallels emphasized here, it was reflected on how Warburg’s teachings contribute to the reading of artistic works after him. Thus, the method of assembly (montage) and association of images was highlighted here, as well as the important relations used by Didi-Huberman when he returns to Warburg in contemporary discussions of art history.